2019
DOI: 10.1039/c9ra07893b
|View full text |Cite
|
Sign up to set email alerts
|

Hollow core–shell structured TS-1@S-1 as an efficient catalyst for alkene epoxidation

Abstract: Hollow core–shell structured TS-1@S-1 with high catalytic performance was synthesized successfully owing to the formation of different titanium active centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…However, the FT-IR result of amorphous titanosilicate showed a much stronger absorption intensity with broadened bands at 3700–3200 cm –1 , indicating the presence of a much higher density of various hydroxyl groups compared to the other TS-1 samples (Figure S10). In addition to these, the amorphous titanosilicate showed strong bands at 1418 and 1580 cm –1 , which might come from the presence of a strong interaction of n -butyl amine with the Lewis acidic sites and Bronsted acidic sites . The FT-IR results thus suggested that the titanosilicate precursor (Scheme ; step 2) is amorphous; however, the resultant samples from the SAC presented evidence of the MFI structure.…”
Section: Resultsmentioning
confidence: 96%
“…However, the FT-IR result of amorphous titanosilicate showed a much stronger absorption intensity with broadened bands at 3700–3200 cm –1 , indicating the presence of a much higher density of various hydroxyl groups compared to the other TS-1 samples (Figure S10). In addition to these, the amorphous titanosilicate showed strong bands at 1418 and 1580 cm –1 , which might come from the presence of a strong interaction of n -butyl amine with the Lewis acidic sites and Bronsted acidic sites . The FT-IR results thus suggested that the titanosilicate precursor (Scheme ; step 2) is amorphous; however, the resultant samples from the SAC presented evidence of the MFI structure.…”
Section: Resultsmentioning
confidence: 96%
“…The TS‐DHBDC‐48h before calcination displays strong characteristic signals at δ = 9.7, 15.4 and 62.8 ppm in Figure 5A, which are assigned to the three carbon species of template TPA + trapped in the zeolite channels. [ 53 ] In addition, the signals of carboxyl group and the C atoms in benzene of 2,5‐dihydroxyterephthalic acid are not detected, indicating that aromatic compounds are detached from TS‐1 during centrifugation following the supernate. This phenomenon proves that the inhibitory effect of DHBDC on the formation of anatase TiO 2 during crystallization and DHBDC is not incorporated into the framework of TS‐1.…”
Section: Resultsmentioning
confidence: 99%
“…[3,4] Among the various metal oxide nanoparticles, ZnO NPs have gained much attention. They are being used in cutting-edge research areas, which account for their wide range of applications in the field of electronics as semiconductors, [5,6] optics, [7] photocatalysts, [8,9] sensors, [10] coating agents in paints and ceramics, [11] as a catalyst in numerous organic reactions, [12] in cosmetics to treat various skin disorders, [13] In the biomedical field, as bioimaging agents, [14] as antibacterial, anti-fungal, and anti-cancer agents. [15][16][17] They are used as efficient adsorbents to remove pollutants.…”
Section: Introductionmentioning
confidence: 99%